The effect of carvedilol on serum and tissue oxidative stress parameters in partial ureteral obstruction induced rat model. Issue 1 (8th November 2012) - Yasar, Adem; Erdemir, Fikret; Parlaktas, Bekir Suha; Atilgan, Dogan; Koseoglu, Resit Dogan; Saylan, Oguzhan; Firat, Fatih
Abstract: Although the pathological mechanism underlying kidney damage is not completely understood, it has been reported that reactive oxygen species (ROS) formed during ureteral obstruction may play an important role in this process. Carvedilol has been used in a limited number of studies examining oxidative injury. The aim of this study was to investigate the effect of carvedilol on serum and tissue oxidative stress parameters in the partial unilateral ureteral obstruction (PUUO)‐induced rat model. To our knowledge, the protective effects of carvedilol in the PUUO‐induced rat model have not been reported. Twenty‐six male Wistar albino rats, age 5.5 to 6 months and weighing 250 to 300 g, were used in this study. The rats were randomly divided into three groups. In Group 1 ( n = 9), the control group, a sham operation was performed. In Group 2 ( n = 8), the PUUO group, the left ureter was embedded into the psoas muscle to create PUUO and maintained for 7 days. In Group 3 ( n = 9), carvedilol was orally administered to the rats (2 mg/kg). After the establishment of PUUO, carvedilol was given for the following 7 days. After partial unilateral ureteral obstruction, a nephrectomy was performed to determine the blood and tissue levels of superoxide dismutase (SOD), malondialdehyde (MDA), protein carbonyl (PC), and nitric oxide (NO). The median SOD, MDA, PC, and NO levels in the tissues were 0.006 U/mg protein, 5.11 nmol/g protein, 4.31 nmol/mg protein, and 0.337 μmol/g protein in the control group, respectively. There was a significant increase in tissue SOD ( p = 0.014), MDA ( p = 0.002), and NO ( p = 0.004) levels in Group 2. However, a statistically significant difference was not observed in PC ( p = 0.847) enzymatic activity in Group 2. When compared with Group 2, carvedilol treatment caused a reduction in NO ( p = 0.003), and PC ( p = 0.001) activities in Group 3. The serum SOD ( p = 0.004), MDA ( p = 0.043), PC ( p = 0.043), and NO ( p = 0.001) levels were significantly different in Group 3 compared with Group 2. Administration of carvedilol also reduced the detrimental histopathologic effects caused by PUUO. According to histopathological examination of the renal tissues, the inflammation rates were 22.2%, 87.5% and 33.3% in Groups 1, 2, and 3, respectively ( p < 0.05). The results of the present study show that partial unilateral ureteral obstruction caused oxidative stress in the serum and kidney tissues of rats, and treatment with carvedilol reduced the harmful effects of ureteral obstruction.